A comprehensive review of etiology, pathophysiologyepidemiology, and management of hair loss and its correlation with COVID-19 - Faraz Changizi; Maryam Abdolmaleki; Mina Farjam; Laya Ohadi (International Journal of Medicine, 2024)
This paper explores the connection between COVID-19 and hair loss, emphasizing its emotional impact. Beyond respiratory effects, the virus causes various skin symptoms, including hair loss (telogen effluvium) in up to one-fifth of patients. The study reviews disruptions in the hair growth cycle induced by COVID-19, suggesting a multifactorial mechanism involving proinflammatory cytokines, the ADE phenomenon, and coagulation cascade activation. Recognizing the psychological impact, the paper uses a comprehensive research methodology to explore the correlation between hair loss and COVID-19. Recommendations for managing COVID-19-induced hair loss include counseling, dietary adjustments, and treatment options like minoxidil and corticosteroids. The study highlights the proactive role of healthcare professionals in addressing COVID-19-related hair loss to enhance patient satisfaction and overall quality of life.